2017
DOI: 10.1007/s13402-017-0334-8
|View full text |Cite
|
Sign up to set email alerts
|

Changes in plasma miR-9, miR-16, miR-205 and miR-486 levels after non-small cell lung cancer resection

Abstract: Our data indicate that miR-9, miR-16, miR-205 and miR-486 may serve as NSCLC biomarkers. The observed cancer-related pre- and post-operative changes in their plasma levels may not only reflect the presence of a primary cancer, but also of a systemic response to cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 37 publications
3
42
0
Order By: Relevance
“…This result was similar to some studies which monitored different microRNAs in serum samples [29,30]. The stimulatory of miR-9 in cancer progression is not only restricted to gastric cancer, since other studies also suggested that the expression of this miRNA could be altered in other human malignancies, including squamous cell carcinoma [31], breast cancer [32] and non-small-cell lung cancer [33]. Wan-Cheng Xiong et al has demonstrated that the up-regulation of miR-9 in colon cancer cells is coupled with the suppression of tumor growth and cancer progression [23].…”
Section: Discussionsupporting
confidence: 89%
“…This result was similar to some studies which monitored different microRNAs in serum samples [29,30]. The stimulatory of miR-9 in cancer progression is not only restricted to gastric cancer, since other studies also suggested that the expression of this miRNA could be altered in other human malignancies, including squamous cell carcinoma [31], breast cancer [32] and non-small-cell lung cancer [33]. Wan-Cheng Xiong et al has demonstrated that the up-regulation of miR-9 in colon cancer cells is coupled with the suppression of tumor growth and cancer progression [23].…”
Section: Discussionsupporting
confidence: 89%
“…Increased expression of miR-223 in NSCLC sputum samples was identified as a non-invasive diagnostic biomarker for NSCLC detection (29). The ectopic expression of miR-9, miR-16, miR-205 and miR-486 in serum specimens collected from patients with NSCLC served as useful diagnostic biomarkers for NSCLC (30). Upregulated expression of miR-411 was shown to have relatively high diagnostic and prognostic value for patients with NSCLC (31).…”
Section: Discussionmentioning
confidence: 99%
“…Li and their team found that miR-9 promotes cell growth and metastasis in LUAD through the repression of TGFBR2 [42], and may serve as biomarker and predicted the prognosis of LUAD. Increase in plasma miR-9 and decrease in miR-486 levels after NSCLC resection may indicate a good prognosis [43]. These data supported that miR-9 and miR-486 may be key therapeutic targets that were related to LUAD malignancy and outcome, while in-depth studies of their operating mechanism are still await for further exploration.…”
Section: Discussionmentioning
confidence: 63%